PERAN ORANG TUA SARANI DALAM PERKEMBANGAN PSIKOSOSIAL REMAJA - Christy Uji Omega Banunaek; Yustinus Windrawanto; Adhi Krisna Maria Agustin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the role of Sarani parents (baptismal sponsors) in the psychosocial development of adolescents at GMIT Imanuel Oenali. The presence of Sarani parents is considered important because they are not only witnesses of baptism but also spiritual companions who are expected to support adolescents in their emotional, social, and identity development. Adolescence is a transitional period characterized by identity exploration and psychosocial challenges, therefore guidance from adult figures is needed. This research used a qualitative method with data collected through in-depth interviews and documentation involving adolescents, Sarani parents, and church leaders. The results show that Sarani parents contribute to adolescents’ psychosocial development through spiritual guidance, emotional support, moral example, and involvement in church activities. Their presence helps adolescents manage emotions, build self-confidence, and develop positive social relationships. However, the study also found challenges such as limited communication and varying levels of involvement from Sarani parents. Overall, collaboration between Sarani parents, biological parents, and the church plays an important role in supporting the healthy psychosocial development of adolescents.